2020
DOI: 10.21203/rs.2.24580/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MMP-13 Enzyme and pH Responsive Theranostic Nanoplatform for Osteoarthritis

Abstract: Stimulus-responsive therapy permits precise control of therapeutic effect only at lesion of interest, which determines it a promising method for diagnosis and imaging-guided precision therapy. The acid environment and overexpressed matrix metalloproteinases-13 (MMP-13) are typical markers in osteoarthritis (OA). However, stimulus-responsive therapeutic platform with high specificity for OA basing on the two markers has not been developed yet. We herein demonstrate a new stimuli-responsive theranostic strategy … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…43 According to clinical and experimental data, there is strong evidence that MMP-13 has a degradative effect on the extracellular matrix and is considered to be an important cofactor or disease mediator in OA. 44,45 In this study, we found that consistent with the increase in M1 macrophages, MMP-13 increased significantly in the OA group. However, after 2 weeks of mechanical loading, there was a reduction in M1 macrophages and the level of MMP-13 was decreased.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…43 According to clinical and experimental data, there is strong evidence that MMP-13 has a degradative effect on the extracellular matrix and is considered to be an important cofactor or disease mediator in OA. 44,45 In this study, we found that consistent with the increase in M1 macrophages, MMP-13 increased significantly in the OA group. However, after 2 weeks of mechanical loading, there was a reduction in M1 macrophages and the level of MMP-13 was decreased.…”
Section: Discussionsupporting
confidence: 77%
“…Synovial macrophages are involved in the production of proinflammatory cytokines and MMPs 43 . According to clinical and experimental data, there is strong evidence that MMP‐13 has a degradative effect on the extracellular matrix and is considered to be an important cofactor or disease mediator in OA 44,45 . In this study, we found that consistent with the increase in M1 macrophages, MMP‐13 increased significantly in the OA group.…”
Section: Discussionsupporting
confidence: 65%
“…Research into enzyme cascade catalysis may provide insight into potential strategies for the development of desired biocompatible DU microenvironment modulator. Enzymes are natural biomaterials capable of catalyzing various chemical reactions to mediate biological processes [ 26 ]. In living organisms, enzyme cascade systems have been evolved by confining cooperating enzymes within compartments to boost their catalytic performances without the separation of intermediates for spatial–temporal modulation of complex physiological microenvironment [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qiumei Lan (Lan et al, 2020) et al developed another MMP/pH-responsive DDS loading psoralidin (PSO) which is extracted from pPoralea corylifolia. The MRC-PPL NPs are designed to target cartilage and respond to MMP-13.…”
Section: Chinese Herb Extracts and Targeted Ddsmentioning
confidence: 99%